2009
DOI: 10.5194/bgd-6-9945-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of grazing on leaf traits and ecosystem functioning in Inner Mongolia grasslands: scaling from species to community

Abstract: Abstract. More attention has focused on using some easily measured plant functional traits to predict grazing influence on plant growth and ecosystem functioning. However, there has been much controversy on leaf traits response to grazing, thus more research should be conducted at the species level. Here we investigated the leaf area, leaf mass and specific leaf area (SLA) of 263 species in eight grassland communities along a soil moisture gradient in the Xilin River Basin, a semiarid grassland of northern Chi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
2
0
1
Order By: Relevance
“…As two of the most important numerical traits that relate to plant relative growth rate and stress tolerance (Westoby, 1998), SLA and plant N content did not show significant responses to grazing. This is in line with an earlier study across Tibetan pastures (Heberling, 2015), but in contrast with positive grazing responses of SLA reported from eastern alpine meadows (Niu et al, 2015) and negative responses in Inner Mongolia (Zheng, Ren, Lan, Li, & Bai, 2010).…”
Section: Grazing Effects On Plant Traits and Fdsupporting
confidence: 92%
“…As two of the most important numerical traits that relate to plant relative growth rate and stress tolerance (Westoby, 1998), SLA and plant N content did not show significant responses to grazing. This is in line with an earlier study across Tibetan pastures (Heberling, 2015), but in contrast with positive grazing responses of SLA reported from eastern alpine meadows (Niu et al, 2015) and negative responses in Inner Mongolia (Zheng, Ren, Lan, Li, & Bai, 2010).…”
Section: Grazing Effects On Plant Traits and Fdsupporting
confidence: 92%
“…This might characterise an escape mechanism from grazing, in particular due to the small leaf size and the high leaf dry matter content, however, in our study, the SLA of juvenile yew needles increased under herbivore pressure and was higher in grazed than in non-grazed saplings. This finding is in agreement which the observation of other authors who confirmed that grazing tolerance can be expressed as high specific leaf area (SLA) and low leaf toughness, which increase shoot regrowth ability and selectivity by herbivores (Zheng et al, 2010).…”
Section: Needle Morphologysupporting
confidence: 82%
“…This finding is surprising because these calculated leaf traits are common predictors of light intensity (Fabjanowski et al, 1974;Zheng et al, 2010), our results therefore indicate that these methods are not suitable to evaluate light conditions of T. baccata stands in small a range of light intensity (between 3 and 16% of full sunlight). Another reason for the lack of correlation could be the distribution of sample points within this range and also the sampling method and sample size.…”
Section: Needle Morphologycontrasting
confidence: 49%